Efforts to Improve Teacher Performance in Learning Through Supervision of Class Visits Post Covid 19 - Siti Handayani (Journal of Business, Social and Technology, 2022)
This study aims to improve teacher performance in learning at SD Negeri 1 Sendang, Karanggede District, Boyolali Regency by using class visit supervision. This research is a school action research. The research was conducted at SD Negeri 1 Sendang, Karanggede District, Boyolali Regency. The research subjects were elementary school teachers from class I to class VI. The research procedure uses two cycles. Data analysis techniques using descriptive analysis techniques. Indicators of achieving the success rate with a minimum score of 75% teachers show high scores following the supervision of post-covid-19 class visits in improving teacher performance. The results of this study indicate that supervision of post-covid-19 class visits can improve teacher performance in learning, this is because through supervision of class visits they feel that they receive input and know the shortcomings in learning. Based on the results of the study, it can be seen that through supervision of post-covid-19 class visits, it can improve teacher performance in learning at SD Negeri 1 Sendang, Karanggede District, Boyolali Regency for the 2021/2022 Academic Year. Thus, it can be concluded that through supervision of post-covid-19 class visits, teachers can improve the performance of teachers in learning at SD Negeri 1 Sendang, Karanggede District, Boyolali Regency.